被膜に著明な石灰化と骨形成を認めた顎下腺多形腺腫の1例 - 岩井, 聡一; 雨河, 茂樹; 米川, 敦子; 小川, 芙美; 永川, 賢治; 大西, 徹郎 (日本口腔外科学会雑誌, 2012)
We report a rare case of pleomorphic adenoma with dystrophic calcification and bone formation in the capsule of the submandibular gland. A 48-year-old man visited our hospital because of a mass in the submandibular gland. CT and FDG-PET images showed a well-defined round mass 20 mm in diameter in the right submandibular gland. It was covered with a calcified substance. The clinical diagnosis was a submandibular tumor, and the patient underwent extirpation of the right submandibular gland. The tumor was histopathologically diagnosed as a pleomorphic adenoma. Histopathologically, the tumor was composed of epithelial and mesenchymal structures including myxomatous and chondroid areas. Dystrophic calcification was observed in the entire periphery of the tumor, and bone formation was seen in contact with the calcified structure.